Description and Economic Evaluation of a “Zero-Waste Mortar-Producing Process” for Municipal Solid Waste Management in Greece - Alexandros Sikalidis; Christina Emmanouil (Journal of Open Innovation: Technology, Market and Complexity, 2019)
The constant increase of municipal solid wastes (MSW) as well as their daily management pose a major challenge to European countries. A significant percentage of MSW originates from household activities. In this study we calculate the costs of setting up and running a zero-waste mortar-producing (ZWMP) process utilizing MSW in Northern Greece. The process is based on a thermal co-processing of properly dried and processed MSW with raw materials (limestone, clay materials, silicates and iron oxides) needed for the production of clinker and consequently of mortar in accordance with the Greek Patent 1003333, which has been proven to be an environmentally friendly process. According to our estimations, the amount of MSW generated in Central Macedonia, Western Macedonia and Eastern Macedonia and Thrace regions, which is conservatively estimated at 1,270,000 t/y for the year 2020 if recycling schemes in Greece are not greatly ameliorated, may sustain six ZWMP plants while offering considerable environmental benefits. This work can be applied to many cities and areas, especially when their population generates MSW at the level of 200,000 t/y, hence requiring one ZWMP plant for processing.